Faktor-Faktor Yang Mempengaruhi Kepuasan Kerja (Studi Pada Pegawai Administratif IKIP PGRI Semarang) - Amirullah, Fatana; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The research objectives to be achieved in this research was todetermine how much of influence individual factors, social factors and the main factorsin the work together on job satisfaction of administrative employees of IKIP PGRISemarang.The results showed that individual factors (X1) had a positive and significantinfluence on job satisfaction (Y). This was evidenced by the results of regression analysisthat demonstrated the value of [tvalue (Sig.) = 0.036] <0.05. Social factors (X2) had apositive and significant impact on job satisfaction (Y). This was evidenced by the resultsof regression analysis that demonstrate the value of [tvalue (Sig.) = 0.001] <0.05. A mainfactor in employment (X3) had a positive and significant influence on job satisfaction (Y).This was evidenced by the results of regression analysis that demonstrated of the value[tvalue (Sig.) = 0.005] <0.05.Based on the results of this study concluded that individualfactors (X1), social factors (X2) and a main factor in the work (X3) either partially orsimultaneously had significant influence on job satisfaction (Y)Keywords: Individual Factor, Social Factor, Main Factor in the jo,Job Satisfaction.